Self-esteem, narcissism, and stressful life events testing for selection and socialization. [article]. - Orth, Ulrich; Luciano, Eva C.
We examined whether self-esteem and narcissism predict the occurrence of stressful life events (i.e., selection) and whether stressful life events predict change in self-esteem and narcissism (i.e., socialization). The analyses were based on longitudinal data from 2 studies, including samples of 328 young adults (Study 1) and 371 adults (Study 2). The effects of self-esteem and narcissism were mutually controlled for each other and, moreover, controlled for effects of depression. After conducting the study-level analyses, we meta-analytically aggregated the findings. Self-esteem had a selection effect, suggesting that low self-esteem led to the occurrence of stressful life events; however, this effect became nonsignificant when depression was controlled for. Regardless of whether depression was controlled for or not, narcissism had a selection effect, suggesting that high narcissism led to the occurrence of stressful life events. Moreover, stressful life events had a socialization effect on self-esteem, but not on narcissism, suggesting that the occurrence of stressful life events decreased self-esteem. Analyses of trait-state models indicated that narcissism consisted almost exclusively of perfectly stable trait variance, providing a possible explanation for the absence of socialization effects on narcissism. The findings have significant implications because they suggest that a person's level of narcissism influences whether stressful life events occur, and that self-esteem is shaped by the occurrence of stressful life events. Moreover, we discuss the possibility that depression mediates the selection effect of low self-esteem on stressful life events. (PsycINFO Database Record. -- (from the authors)